Minsky and the subprime mortgage crisis: The financial instability hypothesis in the era of financialization - Eugenio Caverzasi (Levy Economics Institute of Bard College, 2014)
The aim of this paper is to develop a structural explanation of the subprime mortgage crisis, grounded on the combination of two apparently incompatible financial theories: the financial instability hypothesis by Hyman P. Minsky and the theory of capital market inflation by Jan Toporowski. Our thesis is that, once the evolution of the financial market is taken into account, the financial Keynesianism of Minsky is still a valid framework to understand the events leading to the crisis.
Keywords: B2; B5; E44; G01; 330; Hyman Minsky; Financial Instability Hypothesis; Jan Toporowski; Capital Market Inflation; Financialization; Financial Crisis; Subprime Mortgage Crisis